Aplikasi gelombang ultrasonik untuk pengukuran tingkat kekasaran permukaan beton - Heri Sugito; Diana Layla Riskawati (Youngster Physics Journal, 2017)
The measurement of surface roughness level of matter was done by ultrasonik wave Time-of-Flight methode. The device can be applied to several equirement, such as roughness detection for textile product, sandpaper,asbestos, ceramics, steel and metal industry, etc. The measurement is needed for quality product improvement.  The measurement performed by scanning object which rotated 200 times with stepper motor using ultrasonic transduser. The transduser transmit pulse to object trough transmitter and receiver pulse. The result of scanning displayed in Cathode Ray Osciloscop (CRO) then it used to estimating ToF (Time-of-Flight) by calculating the gap between transmitter pulse and receiver pulse. The objects which measured are tree trunk, concrete A, and concrete B. The reason of selecting the test object is for minimize the atenuation so it can increase the reflection. The result of measurement for average surface roughness of objects are: tree trunk (Ra is minimum 8%, and Ra is maximum 17%), concrete A (Ra is minimum 10%, and Ra is maximum 16%), and concrete B (Ra is minimum 8%, and Ra is maximum 17%).Keywords: surface Roughness, ultrasonic wave, Time-of-Flight